2022
DOI: 10.1002/ardp.202200348
|View full text |Cite
|
Sign up to set email alerts
|

Phthalimide‐tethered imidazolium salts: Synthesis, characterization, enzyme inhibitory properties, and in silico studies

Abstract: A series of new imidazolium salts were prepared in good yield by the reaction between 1-alkylimidazole and a variety of alkyl halides. The structures of the compounds were identified by FT-IR, 1 H NMR, and 13 C NMR spectroscopy, elemental analysis, and mass spectrometry. The crystal structure of 1b was determined by the single-crystal X-ray diffraction method. The phthalimidetethered imidazolium salts exhibited inhibition abilities toward acetylcholinesterase (AChE) and human carbonic anhydrases (hCAs) I and I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 88 publications
0
4
0
Order By: Relevance
“…In order to examine the inhibitory effects of methanol and water extracts of A. alopecurus aerial parts on the hCA II isoform, this isoform was purified by Sepharose-4B-L-Tyrosine-sulfanilamide affinity chromatography from human red blood cells [ 121 ]. Human erythrocyte samples were centrifuged for 30 min at 13,000 rpm for this reason.…”
Section: Methodsmentioning
confidence: 99%
“…In order to examine the inhibitory effects of methanol and water extracts of A. alopecurus aerial parts on the hCA II isoform, this isoform was purified by Sepharose-4B-L-Tyrosine-sulfanilamide affinity chromatography from human red blood cells [ 121 ]. Human erythrocyte samples were centrifuged for 30 min at 13,000 rpm for this reason.…”
Section: Methodsmentioning
confidence: 99%
“…It was observed that 216e (R = 3,5-dinitrobenzoate) was found to be most active agent with IC 50 value of 16.86 nM and 216c (R = 3nitrobenzoate) showed potent inhibitory activity against hCA II with IC 50 value of 15.24 nM [43] (Scheme 24). Molecular docking studies revealed that compound 218h was found to have maximum binding affinity with binding energy of −6.83 kcal/mol [44] (Scheme 25). Pustenko et al developed a new protocol to synthesize 7acylamino-3-H-1,2-benzoxathiepine 2,2-dioxides (226)(227)(228)(229)(230)(231)(232)(233)(234)(235).…”
Section: S C H E M E 17 Synthesis Ofmentioning
confidence: 99%
“…Several phthalimide-based compounds were developed by various research groups ( Figure 1(a) ), which showed appreciable activity against various hCA isozymes. 15 …”
Section: Introductionmentioning
confidence: 99%